2018
DOI: 10.1364/oe.26.006067
|View full text |Cite
|
Sign up to set email alerts
|

All-dielectric planar chiral metasurface with gradient geometric phase

Abstract: Planar optical chirality of a metasurface measures its differential response between left and right circularly polarized (CP) lights and governs the asymmetric transmission of CP lights. In 2D ultra-thin plasmonic structures the circular dichroism is limited to 25% in theory and it requires high absorption loss. Here we propose and numerically demonstrate a planar chiral all-dielectric metasurface that exhibits giant circular dichroism and transmission asymmetry over 0.8 for circularly polarized lights with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
90
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 41 publications
0
90
0
Order By: Relevance
“…It has been recently demonstrated that judicious design of nanopillars carrying in-plane geometrical chirality can potentially result in different coupling of opposite helicities to the waveguide-array modes which in turn leads to their differential response between left-and right-handed circularly polarized lights. 42 Ye et al 43 have shown that multi-mode interference can also arise in metasurfaces made of low-loss metallic nanostructures with finite thickness. Consequently, properly designed metallic nanoposts can support surface plasmon modes whose different interference schemes for opposite helicities yields a giant chiroptical effect.…”
Section: Design Concepts and Device Fabricationmentioning
confidence: 99%
“…It has been recently demonstrated that judicious design of nanopillars carrying in-plane geometrical chirality can potentially result in different coupling of opposite helicities to the waveguide-array modes which in turn leads to their differential response between left-and right-handed circularly polarized lights. 42 Ye et al 43 have shown that multi-mode interference can also arise in metasurfaces made of low-loss metallic nanostructures with finite thickness. Consequently, properly designed metallic nanoposts can support surface plasmon modes whose different interference schemes for opposite helicities yields a giant chiroptical effect.…”
Section: Design Concepts and Device Fabricationmentioning
confidence: 99%
“…Metamaterials that exhibit a wide range of functionalities have been designed over the past few decades [1][2][3][4][5][6]. Of these metamaterials, perfect absorbers offer numerous benefits over conventional absorbers such as increased effectiveness, miniaturisation and the ability to be designed for a specific narrow or broadband range [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Chiral metamaterials and metasurfaces [1][2][3][4][5] have recently attracted much attention in the community of nanophotonics due to their practical applications for circular dichroism (CD), [6][7][8][9][10][11] polarization conversion, [12] chiral biosensing and imaging, [13][14][15] polarimetric detection, [16] spin-controlled wavefront shaping, [17,18] and asymmetric transmission. [10,18,19] Spin-selective optical responses can also be obtained in intrinsically achiral metasurfaces due to extrinsic chirality by the experimental arrangement different from their mirror image [20] and even by the direct phase modulation depending on the handedness of circular polarization of the incident wave. [21] The above metamaterials and metasurfaces can be made of both plasmonic and dielectric materials, the latter of which are preferable due to lower optical losses and stronger CD.…”
Section: Introductionmentioning
confidence: 99%
“…[21] The above metamaterials and metasurfaces can be made of both plasmonic and dielectric materials, the latter of which are preferable due to lower optical losses and stronger CD. [9,10] Over the past decade, nonlinear nanostructures and metasurfaces [22] have extensively investigated for diverse practical applications, including efficient harmonic generation, [23][24][25][26][27][28] four-wave mixing, [29] high-order stimulated Raman scattering, [30] and nonlinear beam shaping. [31] In particular, nonlinear optical processes in chiral metasurfaces [32][33][34][35][36][37][38][39] have great importance for nonlinear chiral sensing and nonlinear metasurface holography.…”
Section: Introductionmentioning
confidence: 99%